(untitled) (Contemporary Mathematics, 2023)
This work purposes to establish a novel analytical method to obtain the atomic solutions of partial differential equations. This will be carried out by employing the tensor product theory in Banach spaces coupled with some properties of atoms operators. Some illustrative examples will be provided to validate our findings.